The Empowerment Effect of Womens Acces to Hygiene and Utilization Status In Rural Areas of East Gojjam Zone Northwest Ethiopia - Haimanot Minwuye Adam; Alemu Azmerawu; Sisay Awoke (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The empowerment has become a common component of water, sanitation, and hygiene (WASH) interventions. However, there is limited evidence on whether access to and utilization of WASH facilities have contributed to the empowerment of women. This study aimed to understand the empowerment effect of women’s access to hygiene and utilization status in selected rural areas of Gozamin and Machakel districts in the East Gojjam Zone, Ethiopia. The analyses were conducted based on responses from 325 married women selected through a multi-stage cluster sampling technique. Gologit2 was used to estimate the correlation between women’s access to hygiene and utilization level and their empowerment status. The gologit2 estimation identified hygiene utilization to have a statistically significant association with women empowerment in terms of self-esteem, household decision-making, and participation in rural health extension activities. A woman with a high hygiene utilization level was 2.5 times more likely to be empowered than a woman with low hygiene utilization level was. However, no statistically significant correlation was found between women’s access to hygiene and their empowerment status. It showed that the mere presence of hygiene facilities did not empower women unless these were actually utilized. Therefore, the researcher recommended that the government strengthen its work to promote and monitor women’s hygiene utilization in addition to the availability of hygiene facilities in the household. Pemberdayaan telah menjadi bagian komponen umum dari air, sanitasi, dan kebersihan (WASH). Namun, ada bukti terbatas tentang apakah akses dan pemanfaatan fasilitas WASH telah berkontribusi pada pemberdayaan perempuan. Penelitian ini bertujuan untuk memahami pengaruh pemberdayaan akses perempuan terhadap status kebersihan dan pemanfaatan di daerah pedesaan terpilih di distrik Gozamin dan Machakel di Zona Gojjam Timur Ethiopia. Analisis kami didasarkan pada tanggapan dari 325 wanita menikah yang dipilih melalui teknik sampling cluster multi-stage. Gologit2 digunakan untuk memperkirakan hubungan antara akses perempuan ke tingkat kebersihan dan pemanfaatan dan status pemberdayaan mereka. Estimasi gologit2 mengidentifikasi pemanfaatan kebersihan memiliki hubungan yang signifikan secara statistik dengan pemberdayaan perempuan dalam hal harga diri, pengambilan keputusan rumah tangga, dan partisipasi dalam kegiatan penyuluhan kesehatan pedesaan. Wanita dengan tingkat pemanfaatan higiene yang tinggi memiliki kemungkinan 2,5 kali lebih besar untuk diberdayakan dibandingkan dengan wanita dengan tingkat pemanfaatan higiene yang rendah. Namun, tidak ditemukan hubungan yang signifikan secara statistik antara akses perempuan terhadap kebersihan dan status pemberdayaannya, yang menunjukkan bahwa keberadaan fasilitas kebersihan saja tidak memberdayakan perempuan kecuali jika fasilitas tersebut benar-benar dimanfaatkan. Kami, oleh karena itu; merekomendasikan agar pemerintah memperkuat pekerjaannya untuk mempromosikan dan memantau pemanfaatan kebersihan oleh perempuan selain ketersediaan fasilitas kebersihan di rumah tangga.